Implementation of the Code Igniter Framework in the Online New Student Admission Application at SMK Muhammadiyah 2 Mertoyudan Magelang - Andre Saputro; Nuryanto; Ardhin Primadewi (Urecol Journal. Part E: Engineering, 2022)
Student admission is one of the processes that exist in educational institutions. Schools accept students by selecting grades, achievements, and other factors. SMK Muhammadiyah 2 Mertoyudan located in Magelang Regency conducts semi-manual PPDB by compiling ledger records and spreadsheets. The school has difficulty getting PPDB historical data and PPDB reporting. Besides the CPDB has difficulty monitoring registration data directly. The PPDB application is developed with the Code Igniter framework with main features that can be accessed by 3 actors (PPDB manager, CPDB and admin). Applications can store historical data, provide convenience with all forms of custom PPDB reporting and can be accessed online by CPDB and CPDB trustees. From the results of the user acceptance test carried out on schools and CPDB, an assessment of 84.8% was obtained which showed that respondents were satisfied with the functionality of the online PPDB application.